Product Development Categorized as Independent Strategic and Innovative Practice: Case from Indian Manufacturing - Dutt, Himanshu (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
In recent time, Indian manufacturing has seen technologically intensive and resource optimization based initiatives to satisfy competitive urge and to build or sustain market position. This they do by developing products either strategically or innovatively, but that is hardly distinguished or seen as a separate approach to product development. Strategically, product development is resource optimization based while innovatively, it is product differentiation focused. This paper outlines the strategic and innovative approach to product development and analyzes sector specific role of each in product development. The study is undertaken with nine product development team-leaders and resource-heads, three of each from automobile, steel and textile. It is concluded that textile is strategically skewed toward product development whereas automobile is inclined towards innovative orientation. The biggest limitation of this study is smaller sample-size because respondents are reluctant to disclose new technical initiatives and composition of product development.